Impact of Kinesio Taping on Oral Feeding and Swallowing Functions: Acoustic Analysis of Swallowing Sounds in Late Preterm Infants—A Randomized Clinical Trial - Nilay Comuk Balci; Deniz Anuk Ince; Ayşe Ecevit; Balkar Erdoğan; Ilknur Ezgi Doğan; Ozden Turan; Aylin Tarcan (Children)
Background/Objectives: Feeding difficulties in late preterm infants are a major factor contributing to prolonged hospitalization and re-admission. Early support for the sucking and swallowing muscles may accelerate their maturation, facilitating safe and early discharge. This study aims to evaluate the effects of the Kinesio-taping technique on feeding muscles and assess feeding and swallowing function in late preterm infants through the acoustic analysis of swallowing sounds. Methods: Seventy-four late preterm infants (mean gestational age 35.30 ± 0.81 weeks) were randomly assigned to either a Kinesio-taping group or a control group. A single physiotherapist applied Kinesio taping to support the masseter and hyoid muscles, using a facilitatory technique to enhance muscle function. The Kinesio taping was removed two days after its application. The amount of milk intake, the time for milk intake, oxygen saturation during milk intake, the number of days required for transition to full oral feeding, the length of hospital stay, the duration of oxygen requirement, the maximum number of rhythmic swallows, and the heart rate during milk intake were recorded using a digital stethoscope before and two days after Kinesio-taping application. The collected data were assessed through acoustic analysis. Results: No statistically significant differences were observed between the Kinesio-taping and control groups regarding milk intake amount, feeding duration, oxygen saturation during feeding, the transition time to full oral feeding, the length of hospital stay, or the duration of oxygen support (p > 0.05). However, a significant difference was found between the groups in the maximum number of rhythmic swallows during feeding and the heart rate during milk intake (p < 0.05). Conclusions: The application of the Kinesio-taping technique showed no adverse effects on preterm infants in the NICU during the feeding skills intervention. The assessment of acoustic analysis revealed a significant difference in the maximum number of rhythmic swallows and heart stabilization during feeding in the Kinesio-taping group. Further studies are warranted, incorporating different application types and techniques with larger sample sizes, especially among preterm infants with an early gestational age in the NICU, to stabilize the suck and swallow muscles.